Culture in the domains of law - Provost,Rene,Ed (Cambridge studies in law and society, 2017)
"What does it mean for courts and other legal institutions to be culturally sensitive? What are the institutional implications and consequences of such an aspiration? To what extent is legal discourse capable of accommodating multiple cultural narratives without losing its claim to normative specificity? And how are we to understand meetings of law and culture in the context of formal and informal legal processes, when demands are made to accommodate cultural difference? The encounter of law and culture is a polycentric relation, but these questions draw our attention to law and legal institutions as one site of encounter warranting further investigation, to map out the place of culture in the domains of law by relying on the insights of law, anthropology, politics, and philosophy. Culture in the Domains of Law seeks to examine and answer these questions resulting in a richer outlook on both law and culture"--